2020
DOI: 10.1111/mpp.13004
|View full text |Cite
|
Sign up to set email alerts
|

A conserved double‐W box in the promoter of CaWRKY40 mediates autoregulation during response to pathogen attack and heat stress in pepper

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 69 publications
0
25
0
Order By: Relevance
“…An increasing number of studies have shown that WRKY TFs can positively respond to the tolerance of plants to high temperatures. For example, CaWRKY40 in pepper participates in the response of plants to high-temperature stress [ 89 ], and the overexpression of CaWRKY40 reduces the sensitivity of tobacco to high-temperature treatment, whereas the loss of this TF reduces this tolerance [ 90 ]. Similar results were found for CaWRKY40 and GhWRKY39 , expressed in upland cotton [ 91 , 92 ].…”
Section: Wrky Tfs In Response To High Temperaturementioning
confidence: 99%
“…An increasing number of studies have shown that WRKY TFs can positively respond to the tolerance of plants to high temperatures. For example, CaWRKY40 in pepper participates in the response of plants to high-temperature stress [ 89 ], and the overexpression of CaWRKY40 reduces the sensitivity of tobacco to high-temperature treatment, whereas the loss of this TF reduces this tolerance [ 90 ]. Similar results were found for CaWRKY40 and GhWRKY39 , expressed in upland cotton [ 91 , 92 ].…”
Section: Wrky Tfs In Response To High Temperaturementioning
confidence: 99%
“…A previous study indicated that AtWRKY52 (group III member) in Arabidopsis thaliana confers resistance to the bacterial soil-borne pathogen R. solanacearum (Deslandes et al, 1998 , 2002 ). CaWRKY28, CaWRKY30 (group III member), CaWRKY40, CaWRKY41 (group III member), and CaWRKY58 in pepper regulated the defense response to R. solanacearum in plants (Wang et al, 2012 ; Muhammad et al, 2018 ; Dang et al, 2019 ; Hussain et al, 2021 ; Liu et al, 2021 ; Yang et al, 2021 ). Overexpression of sugarcane class III WRKY5 increased bacterial wilt resistance (Wang et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…The cis-elements analysis of the promoter sequence of CmGLP2-5 (2000 bp) found that its promoter sequence contained a large number of MYB-binding sites and W-box ( Figure 4 ). Among them, W-box is considered to be the potential binding site of the WRKY transcription factor [ 31 , 32 , 33 ]. We cloned a fragment P in the CmGLP2-5 promoter, which contains a W-box and three MYB-binding sites ( Figure 7 A).…”
Section: Resultsmentioning
confidence: 99%